2014
DOI: 10.1080/09297049.2014.917619
|View full text |Cite
|
Sign up to set email alerts
|

Receptive vocabulary and semantic knowledge in children with SLI and children with Down syndrome

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 66 publications
(86 reference statements)
1
32
0
2
Order By: Relevance
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
“…One study verified that individuals with DS showed a significant deficit in the semantic knowledge, which is an indicator of dissociation between image-word correspondence 25 . However, the use of one-dimensional material is part of the they attend, to provide a desirable communication between their pairs and favor learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations